2014
DOI: 10.1007/s00417-014-2756-6
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vessel diameter in normal-tension glaucoma patients with asymmetric progression

Abstract: In our series of NTG patients with asymmetric progression, central retinal artery diameter decreased over time in the progressed eyes, whereas no significant decrease in the central retinal artery diameter was seen in the stable eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…More recently, Lee et al compared 27 eyes with bilateral NTG who showed asymmetrical glaucoma progression after a mean follow-up of 24.3 months and found significant narrowing of retinal arteriolar calibre in progressed eyes but not in contralateral stable eyes. 102 No correlation was found for retinal venular calibre, however, they hypothesised this may be due to clinically asymptomatic engorgement of venous blood flow in glaucoma, together with different regulatory mechanisms governing changes in retinal artery and vein diameters. 102 No significant intereye difference was observed in the mean baseline vessel calibre between progressed and stable eyes.…”
Section: Longitudinal Relationship Between Retinal Vascular Changes Wmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Lee et al compared 27 eyes with bilateral NTG who showed asymmetrical glaucoma progression after a mean follow-up of 24.3 months and found significant narrowing of retinal arteriolar calibre in progressed eyes but not in contralateral stable eyes. 102 No correlation was found for retinal venular calibre, however, they hypothesised this may be due to clinically asymptomatic engorgement of venous blood flow in glaucoma, together with different regulatory mechanisms governing changes in retinal artery and vein diameters. 102 No significant intereye difference was observed in the mean baseline vessel calibre between progressed and stable eyes.…”
Section: Longitudinal Relationship Between Retinal Vascular Changes Wmentioning
confidence: 99%
“… 102 No correlation was found for retinal venular calibre, however, they hypothesised this may be due to clinically asymptomatic engorgement of venous blood flow in glaucoma, together with different regulatory mechanisms governing changes in retinal artery and vein diameters. 102 No significant intereye difference was observed in the mean baseline vessel calibre between progressed and stable eyes.…”
Section: Longitudinal Relationship Between Retinal Vascular Changes Wmentioning
confidence: 99%
“…Previously, our group reported that the central retinal arteriolar equivalent (CRAE) decreased over time in the progressed eyes, whereas no significant decrease was seen in the stable eyes in patients with bilateral normal-tension glaucoma (NTG). 7 Other studies by our group showed that patients with NTG had smaller diameters of the central retinal vessels than healthy subjects, 8 and the mean CRAE was smaller in the NTG than in the high-tension glaucoma group. 9 In those studies, most patients were categorized into early stage of glaucoma (mean deviation ‡ -6 dB).…”
mentioning
confidence: 61%
“…The FAZ in the progressed NTG group was larger than that in the control group, similar to a previous study [30], except the larger FAZ in the current study occurred before significant NTG development. Since circulation is an important factor for the occurrence and progression of NTG, rather than prominent high IOP [31, 32], more extensive vascular defects could be possible for impending NTG compared to HTG. Outer retinal perfusion was lower in the progressed HTG group than the control group, while similar choriocapillaris perfusion may be because the choroid is not the major site of glaucoma damage.…”
Section: Discussionmentioning
confidence: 99%